Variable effects of alpha v suppression on VEGFR-2 expression in endothelial cells of different vascular beds - Dardik, Rima; Livnat, Tami; Seligsohn, Uri (Thrombosis and Haemostasis, 2009)
Integrins αvβ3 and αvβ5 have been long considered as proangiogenic receptors, yet genetic ablation studies demonstrated enhanced angiogenesis in mice lacking αvβ3 and αvβ5 integrins, which was attributed to increased expression of vascular endothelial growth factor receptor-2 (VEGFR-2). In this study, we determined the effect of αvβ3 and αvβ5 suppression in endothelial cells (EC) on vascular endothelial growth factor (VEGF) and VEGFR-2 expression. αv was suppressed by shRNA in HUVEC (venous endothelial cells) and HMVEC (microvascular endothelial cells).VEGFR-2 was significantly upregulated by αv suppression in HUVEC and downregulated in HMVEC at both mRNA and protein levels,as assessed by real-time PCR and flow cytometry,respectively.HMVEC displayed completely abolished Sp1 binding to the VEGFR-2 promoter, and HUVEC exhibited enhanced binding to the –170 E- Box element in the VEGFR-2 promoter, assessed by electrophoretic mobility shift assay. Realtime PCR also revealed opposite effects on the expression of 5 additional important genes involved in angiogenesis in the two cell types.VEGF mRNA expression was enhanced in HUVEC and reduced in HMVEC; however, these alterations were not statistically significant.VEGF-induced proliferation was upregulated in HUVEC and reduced in HMVEC following αv suppression. No tube formation on Matrigel was observed in αv suppressed cells, regardless of their origin.These results indicate that suppression of αv integrins can either augment or inhibit VEGFR-2 levels and VEGF-induced proliferation in EC from different vascular beds. Hence, therapeutic antiangiogenic intervention by siRN-Amediated suppression of αv integrins should take into account variable and potentially hazardous responses in different vascular beds.
Keywords: Angiogenesis; αvβ3 and αvβ5 integrins; αvβ3 and αvβ5 inhibitors; αv suppression; siRNA